2020
DOI: 10.1080/13506129.2020.1765768
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response to single agent daratumumab is associated with improved progression-free survival in relapsed/refractory AL amyloidosis

Abstract: BackgroundDaratumumab is a monoclonal antibody, which targets CD38; an antigen expressed on malignant plasma cells in AL amyloidosis thus providing a rationale for its use. MethodPatients treated with daratumumab monotherapy (2016)(2017)(2018)(2019) for relapsed / refractory systemic AL amyloidosis were identified from the database at the UK National Amyloidosis Centre. ResultsOf 50 evaluable patients, haematological responses at 3 months were: CR -19 (38%), VGPR -14 (28%), PR -9 (18%) and no response -8 (16%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Early reports suggested a high response rate (76%) in heavily pretreated patients 78 . These data were confirmed by a number of other retrospective studies 79 81 . Two prospective phase II studies of daratumumab in combination with dexamethasone for relapsed AL amyloidosis have been with encouraging results.…”
Section: Introductionsupporting
confidence: 77%
“…Early reports suggested a high response rate (76%) in heavily pretreated patients 78 . These data were confirmed by a number of other retrospective studies 79 81 . Two prospective phase II studies of daratumumab in combination with dexamethasone for relapsed AL amyloidosis have been with encouraging results.…”
Section: Introductionsupporting
confidence: 77%
“…In the phase 3 ANDROMEDA trial, subcutaneous daratumumab plus bortezomib, cyclophosphamide, and dexamethasone showed efficacy and safety in newly diagnosed AL amyloidosis [ 16 , 17 ]. Dara-containing regimens also appeared to be highly active in patients with relapsed/refractory AL amyloidosis, providing rapid hematological responses with a good safety profile [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Although different studies have been reported in the literature, most are case reports, and real-life clinical studies are needed to confirm the efficacy and toxicities of Dara therapeutic regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Milani and Palladini [7] supplies us with a very well-organized review on the value of conventional therapy in amyloidosis. The readers will also enjoy the review of Van Doren and Lentzsch [8], which leads us through nonchemotherapy treatments of amyloidosis and presents data on the current standard of care, VCd, as well as emerging evidence of the important role of daratumumab [9][10][11][12], which may define the new standard of care [13]. Sanchorawala [14], who arguably have the world's greatest experience, provide a comprehensive review about the timing and role of autologous stem cell transplantation in amyloidosis, as well as selection criteria.…”
mentioning
confidence: 99%